Investment facilitation: leaving the past behind - Felipe Hees; Henrique Choer Moraes; Pedro Mendonça Cavalcante; Pedro Barreto da Rocha Paranhos (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2018)
WTO discussions on investment facilitation have drawn attention to an issue that directly contributes to improving domestic governance, without reviving the negative experience of past multilateral investment discussions. This Perspective advances this conversation with elements from the Brazilian experience with signing investment agreements, in which facilitation is a key feature.
Keywords: 330